A multi-herd study shows that saliva is more than a reflection of serum biomarkers in pigs - J. Sánchez (Elsevier, 2021)
This study evaluates if biomarkers of porcine health status in saliva samples is a mere reflection of serum to detect disease in pigs under field conditions. Four farms from the same commercial company were included to obtain samples from animals with different pathological conditions. A total of 10 healthy animals and 10–15 animals from each farm with clinical symptoms of the disease were sampled for paired saliva and blood during a veterinary clinical visit. The biomarker panel included acute-phase proteins (APPs), C-reactive protein (CRP), haptoglobin (Hp), an inflammatory marker, adenosine deaminase (ADA), the total antioxidant capacity (TAC), the levels of essential trace elements, copper (Cu) and zinc (Zn), and the measurement of the total protein content (TP). After detailed statistical analysis, the results showed that saliva could replace serum for APP measurements since a good agreement has been observed between the concentrations of APPs in both body fluids. For any other biomarker, no agreement between the concentrations quantified in serum and saliva samples was observed visually. However, salivary ADA and TP concentrations were statistically significantly higher in the diseased, whereas the statistical tests with serum concentrations were inconclusive. Furthermore, greater differentiation between healthy and diseased animals could be observed when the distribution of biomarkers was analysed in saliva than in other serum samples. The diagnostic power to discriminate between healthy and diseased pigs is similar in saliva and in serum samples. Preliminary regression models may offer an optimal combination of biomarkers for disease detection in saliva (Hp, CRP, and TAC) and serum (Hp, CRP, and Cu), which demands less labour, sample, and financial cost for saliva determinations. The contradictory results observed for TAC, Cu, and Zn levels between body fluids indicate a need for further studies. To sum up, saliva-based biomarkers instead of serum-based biomarkers could contribute to more efficient detection of diseased animals.